Antitumoral and Antimicrobial Activities of Block Copolymer Micelles Containing Gold Bisdithiolate Complexes - Andreia Sousa; Joana F. Santos; Francisco Silva; Sílvia A. Sousa; Jorge H. Leitão; António P. Matos; Teresa Pinheiro; Rafaela A. L. Silva; Dulce Belo; Manuel Almeida; Fernanda Marques; Célia Fernandes (MDPI AG, 2023)
Gold(III) bisdithiolate complexes have been reported as potential antimicrobial and antitumoral agents. The complex [Au(cdc)2]− (cdc=cyanodithioimido carbonate) displayed antimicrobial and outstanding antitumor activity against the ovarian cancer cells A2780 and A2780cisR, which are sensitive and resistant to cisplatin, respectively. However, poor water solubility may hamper its clinical use. Block copolymer micelles (BCMs) may solubilize hydrophobic drugs, improving their bioavailability and circulation time in blood. Aiming to provide water solubility, prolonged availability, and enhanced therapeutic indexes, BCMs loaded with [Au(cdc)2]− were synthesized and characterized. The BCM-[Au(cdc)2] micelles were prepared with a loading efficiency of 64.6% and a loading content of 35.3 mg [Au(cdc)2]−/gBCM. A hydrodynamic diameter of 77.31 ± 27.00 nm and a low polydispersity index of 0.18 indicated that the micelles were homogenous and good candidates for drug delivery. Cytotoxic activity studies against A2780/A2780cisR cells showed that BCM-[Au(cdc)2] maintained relevant cytotoxic activity comparable to the cytotoxicity observed for the same concentration of gold complexes. The Au uptake in A2780 cells, determined by PIXE, was ca. 17% higher for BCMs-[Au(cdc)2] compared to [Au(cdc)2]−. The BCMs-[Au(cdc)2] presented antimicrobial activity against S. aureus Newman and C. glabrata CBS138. These results evidenced the potential of BCM-[Au(cdc)2] for drug delivery and its promising anticancer and antimicrobial activities.